2002
DOI: 10.1016/s0008-6363(02)00511-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of cardiac protein kinase C isozyme expression after aortic banding in rat

Abstract: This study characterizes in the right and left ventricle a differential regulation of the dominant PKC isozymes in pressure-overload cardiac hypertrophy both at the protein and the mRNA level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 54 publications
3
24
0
3
Order By: Relevance
“…Also, direct stimulation of PKC by phorbol esters mimicked the hypertrophic actions of NE (37). Aortic banding caused an upregulation of certain Ca 2+ -dependent and Ca 2+ -independent PKC isozymes in the LV and, after a delay, also in the RV (32). A similar delay of the RV response was observed in the present study with regard to the hypertrophic phenotype and also to the potentiation of the PDB-evoked PLD activation.…”
Section: +supporting
confidence: 86%
See 1 more Smart Citation
“…Also, direct stimulation of PKC by phorbol esters mimicked the hypertrophic actions of NE (37). Aortic banding caused an upregulation of certain Ca 2+ -dependent and Ca 2+ -independent PKC isozymes in the LV and, after a delay, also in the RV (32). A similar delay of the RV response was observed in the present study with regard to the hypertrophic phenotype and also to the potentiation of the PDB-evoked PLD activation.…”
Section: +supporting
confidence: 86%
“…The RV hypertrophied much later, namely, >100 days after banding. A similar sequential LV and delayed RV hypertrophy following aortic banding had been described before (32). In the hypertrophic LV 30 -50 days after banding, the PLD activation caused by the α1-adrenoceptor agonist PE and by the phorbol ester PDB were markedly potentiated, whereas the basal PLD activity was only slightly increased.…”
Section: Discussionsupporting
confidence: 75%
“…2 However, previous studies have found increased or unaltered activation and expression of PKC-␣ in experimental models of LVH and CHF. 18,27,28 These divergent findings may relate to the duration (acute/compensated versus chronic/ end-stage) and/or etiology (myocardial infarction, pressure overload, volume overload, genetic hypertension) of heart disease. For these reasons, we examined PKC-␣ expression and activation in left ventricles obtained from rats in early HF and end-stage CHF.…”
Section: Pkc-␣ Expression and Activation In Experimental Chfmentioning
confidence: 99%
“…Previous studies have reported that the PKC␦ and -ε isoforms play an important role in cardiac hypertrophy (4,32). The PKCε activates ERK-AP-1 signaling pathway, leading to myocardial hypertrophy and increases in protein synthesis (28).…”
Section: Discussionmentioning
confidence: 99%